Safety in numbers: developing a shared analytics service for academic libraries. Issue 1 (8th July 2014) - Showers, Ben; Stone, Graham
Abstract : Purpose: – It is clear that libraries consider the use of data to inform decision making a top priority in the next five years. JISC's considerable work on activity data has highlighted the lack of tools and services for libraries to exploit this data. The purpose of this paper is to explore the potential of a shared analytics service for UK academic libraries and introduce the JISC Library Analytics and Metrics Project. The project aims to help libraries effectively management collections and services as well as delivering pre-emptive indicators and "actionable insights" to help identify new trends, personalise services and improve efficiencies, economies and effectiveness (student attainment and satisfaction and institutional reputation, for example). The project builds on the Library Impact Data Project at the University of Huddersfield and the work of the Copac Activity Data and Collections Management tools. The paper will deliver a case study of the project, its progress to date, the challenges of such an approach and the implications the service has for academic libraries. Design/methodology/approach: – The paper will be a case study of the project and its institutional partners and early adopters work to date and explore both the technical and cultural challenges of the work as well as its implications for the role of the library within the institution and the services it provides. Specifically the case study will comprise of the following aspects: a brief history of the work and the context of library analytics services in the UK (and internationally). A description of the approach adopted by the project, and the vision and goals of the project. Exploration of the challenges associated with the project. Outline of the implications of the project and the resultant service. Findings: – This paper will report on the initial findings of the project, which will run from January to December 2013. In particular it will consider the issues surfaced through the close engagement with the academic library community (through the projects community advisory and planning group) and the institutional early adopters around data gathering and analysis. Practical implications: – Data accumulated in one context has the potential to inform decisions and interventions elsewhere. While there are a number of recognised and well-understood use cases for library analytics these tend to revolve around usage and collection management. Yet, the potential of a shared analytics service is in uncovering those links and indicators across diverse data sets. The paper will consider a number of practical impacts: performance – benchmarking, student attainment and research productivity; design – fine tuning services, personalised support; trends – research landscape, student marketplace, utilisation of resources. The case study will explore these practical implications for libraries and what they mean for the future of the library within the academy. Originality/value: – The paper will present a case study of a unique service that currently fills an important gap within the library analytics space. The paper will focus on the services potential to transform both the way the library works and how it is perceived by its users, as well as its role and relationship within the broader institution.